Electrophoretic fluid, method for preparing the same, electronic paper module, and display device
Patent Information
- Application Number
- CN202610966664.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]本申请的目的在于提供一种电泳液及其制备方法、电子纸模组、显示装置,旨在解决如何使电泳液不依赖交变电场控制、而能够随剪切速率自适应调节流变状态以更好地提高显示效果的技术问题
[0018]本申请第一方面提供的电泳液中包括一定含量组分的黑色电泳粒子、白色电泳粒子、剪切变稀聚合物、分散稳定剂、电荷控制剂和溶剂;其中,剪切变稀聚合物具有剪切变稀型非牛顿流体特性,其在无外加交变电场条件下可形成较为松散的三维物理网络结构,具有显著的剪切变稀行为(即高剪切速率下黏度降低、低剪切速率下黏度高的流变调控),而本申请在该剪切变稀聚合物基础上,基于各组分含量形成的具有剪切变稀型非牛顿流体特性的电泳液,不仅具有快速响应和低残影的特点,而且具有很好的稳态保持性能,同时功耗低;将本申请的电泳液用在电子纸中,可以显著提升电子纸的显示性能,具有很好的应用前景。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application belongs to the field of electrophoretic display technology, and particularly relates to an electrophoretic solution and its preparation method, an electronic paper module, and a display device. Background Technology
[0002] Electronic paper (E-paper) achieves black-and-white or color display through the directional migration of charged particles in an electrophoretic solution. Traditional electrophoretic solutions often exhibit Newtonian fluid properties, meaning that the shear stress at any point is linearly related to the shear deformation rate, and the viscosity does not change with the shear rate.
[0003] The Newtonian fluid properties of electrophoretic fluid bring the following problems to display control: (1) Limited refresh rate: Under a fixed viscosity, the particle migration speed is limited, making it difficult to complete the full screen refresh in a short time. (2) Image retention: After the refresh stops, the particles continue to migrate slowly due to inertia and Brownian motion, resulting in background contamination. (3) Unstable power consumption: In order to increase the speed, the driving voltage needs to be increased, which increases energy consumption and accelerates device aging. Summary of the Invention
[0004] The purpose of this application is to provide an electrophoretic solution and its preparation method, an electronic paper module, and a display device, aiming to solve the technical problem of how to make the electrophoretic solution adaptively adjust its rheological state with the shear rate to better improve the display effect without relying on the control of alternating electric fields.
[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides an electrophoresis solution, wherein, based on the total mass of the electrophoresis solution as 100%, the electrophoresis solution comprises the following components in mass percentage: Black electrophoretic particles 6-8%; White electrophoretic particles 6-8%; Shear-thinning polymers: 2-8%; Dispersant stabilizer 0.8~1.5%; Charge control agent 0.2~1.2%; The remaining amount is solvent; The shear-thinning polymer exhibits shear-thinning non-Newtonian fluid properties.
[0006] In some embodiments, at least a portion of the shear-thinning polymer is coated onto at least a portion of the surface of the black electrophoretic particles to form a coating layer, and / or at least a portion of the shear-thinning polymer is coated onto at least a portion of the surface of the white electrophoretic particles to form a coating layer.
[0007] In some embodiments, the number-average molecular weight of the shear-thinning polymer is 10,000 to 100,000.
[0008] In some embodiments, the shear-thinning polymer is an amorphous organic polymer.
[0009] In some embodiments, the molecular structure of the shear-thinning polymer contains functional groups, which form reversible physical crosslinks through at least one of hydrogen bonding, π–π stacking, and zwitterionic interaction.
[0010] In some embodiments, the functional group includes at least one of ureidopyrimidinone terminal group, N,N'-bis(C6~14 alkyl)ureido, ureo, pyrene methyl, and sulfobetaine.
[0011] In some embodiments, the shear-thinning polymer includes at least one of ureidopyrimidinone-terminated poly(lauryl methacrylate), N,N'-bis(dodecyl)urea-grafted poly(stearyl methacrylate), 1-pyrene methyl methacrylate-lauryl methacrylate copolymer, and sulfobetaine-functionalized poly(dodecyl methacrylate).
[0012] In some embodiments, the solvent includes an ionic liquid or an organic solvent; wherein the ionic liquid includes at least one of imidazolium ionic liquids, pyridinium ionic liquids, quaternary ammonium salt ionic liquids, quaternary phosphonium salt ionic liquids, and pyrrolidine ionic liquids, and the organic solvent includes an alkane solvent.
[0013] In some embodiments, the black electrophoretic particles include at least one of carbon black, copper chromium black, and iron manganese black; And / or, the white electrophoretic particles include at least one of titanium dioxide, silicon dioxide, and aluminum oxide.
[0014] Secondly, this application provides a method for preparing an electrophoresis solution, comprising: Provide the components of the electrophoresis solution provided in the first aspect of this application; The shear-thinning polymer is mixed with the black electrophoretic particles and the white electrophoretic particles to obtain coated particles; The coated particles and the charge control agent are mixed for charge regulation, then added to the solvent, and the dispersing stabilizer is added to obtain the electrophoretic solution.
[0015] In some embodiments, the mixing process includes: dissolving the shear-thinning polymer in a portion of the solvent to obtain a polymer mother liquor with a mass percentage of 4% to 6%, and then dividing the polymer mother liquor into two portions and mixing and stirring them separately with the black electrophoretic particles and the white electrophoretic particles.
[0016] Thirdly, this application provides an electronic paper module, wherein the electronic paper module is filled with the electrophoretic solution provided in the first aspect of this application or the electrophoretic solution prepared by the preparation method provided in the second aspect of this application.
[0017] Fourthly, this application provides a display device, including the electronic paper module provided in the third aspect of this application.
[0018] The electrophoretic solution provided in the first aspect of this application includes black electrophoretic particles, white electrophoretic particles, a shear-thinning polymer, a dispersion stabilizer, a charge control agent, and a solvent in a certain amount. The shear-thinning polymer exhibits shear-thinning non-Newtonian fluid properties, forming a relatively loose three-dimensional physical network structure under conditions without an external alternating electric field, and exhibits significant shear-thinning behavior (i.e., rheological regulation of reduced viscosity at high shear rates and high viscosity at low shear rates). Based on this shear-thinning polymer, this application provides an electrophoretic solution with shear-thinning non-Newtonian fluid properties, formed according to the content of each component. This solution not only features rapid response and low image retention but also excellent steady-state retention performance, while also exhibiting low power consumption. Using this electrophoretic solution in electronic paper can significantly improve the display performance of electronic paper, demonstrating promising application prospects.
[0019] The electrophoretic solvent preparation method provided in the second aspect of this application involves first coating and modifying a shear-thinning polymer with black and white electrophoretic particles to obtain coated particles. Then, the coated particles are mixed with a charge control agent, a solvent, and a dispersant stabilizer to form the electrophoretic solvent. This preparation method is not only simple and easy to scale up, but also produces an electrophoretic solvent with shear-thinning non-Newtonian fluid characteristics. It exhibits fast response, low image retention, excellent steady-state retention, and low power consumption. Based on the composition of each component, the resulting electrophoretic solvent with shear-thinning non-Newtonian fluid characteristics shows great promise for application in the field of electronic paper.
[0020] The electronic paper module provided in the third aspect of this application contains an electrophoretic liquid unique to this application. This electrophoretic liquid can exhibit significant shear-thinning behavior under conditions without an external alternating electric field, thereby enabling the electronic paper module to display advantages such as fast response speed, low image retention, and good steady-state retention performance.
[0021] The display device provided in the fourth aspect of this application includes the electronic paper module unique to this application, thereby having excellent display performance.
[0022] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the shear-thinning polymer in the electrophoresis solution provided in this application under different shear states.
[0025] Figure 2 This is a schematic diagram of the preparation method of the electrophoresis solution provided in this application.
[0026] Figure 3 This is a comparison graph of the viscosity of the electrophoretic solution as a function of shear rate in Example 3 and Comparative Example 1 of this application.
[0027] Figure 4 These are fast-scroll display images of the electrophoresis solutions of Examples 1-10 and Comparative Examples 1-3 of this application. Detailed Implementation
[0028] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0029] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0030] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0031] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0032] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0033] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a well-known unit of mass in the chemical industry, such as µg, mg, g, or kg.
[0034] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.
[0035] Currently, methods for improving the Newtonian fluid properties of electrophoretic fluids mainly focus on particle surface modification and charge control agent optimization. However, these methods are generally static adjustments, making it difficult to dynamically switch the rheological properties of the electrophoretic fluid at different driving stages. Furthermore, the applicant previously disclosed a technique that uses electrorheological effects to switch the electrophoretic fluid between Newtonian and non-Newtonian fluid states. This technique works by inducing the formation or destruction of structures in electrorheological materials through an alternating electric field, thereby controlling the rheological state. However, this approach requires additional alternating electric field control conditions, and its rheological response process depends on polarization and structural rearrangement. Under multiple refresh conditions in electronic paper, there is a problem of image retention accumulating with each refresh, thus affecting the display effect.
[0036] Current techniques for switching electrophoretic solutions between Newtonian and non-Newtonian fluid states via electrorheological effects require additional electric field control. Furthermore, their rheological response depends on polarization and structural rearrangement, leading to image retention issues that accumulate with each refresh in electronic paper applications, thus affecting display quality. Therefore, this application develops an electrophoretic solution and its preparation process that do not rely on alternating electric field control and can adaptively adjust their rheological state with shear rate. This reduces image retention under repeated refresh conditions and can improve display performance when used in electronic paper modules and display devices. The specific technical solution is as follows.
[0037] Firstly, embodiments of this application provide an electrophoresis solution. Specifically, based on the total mass of the electrophoresis solution being 100%, the electrophoresis solution of this application embodiment comprises the following components by mass percentage: Black electrophoretic particles 6-8%; White electrophoretic particles 6-8%; Shear-thinning polymers: 2-8%; Dispersant stabilizer 0.8~1.5%; Charge control agent 0.2~1.2%; The remaining amount is solvent; Among them, shear-thinning polymers exhibit shear-thinning non-Newtonian fluid properties.
[0038] The electrophoretic solution provided in this application is a non-Newtonian fluid (shear-thinning) electrophoretic solution. By introducing a shear-thinning polymer that can form a loose network structure into the solvent system, it exhibits different viscosities at different shear rates: (1) Low-speed driving or static state: The shear-thinning polymer network structure is stable, which can reduce the migration of electrophoretic particles and reduce afterimages; (2) High-speed refresh stage: High-speed shearing can partially dissociate the weak interactions between polymer chains, reduce the degree of chain entanglement, and cause the polymer chains and the surrounding coating structure of particles to orient and partially deconstruct, thereby reducing the network resistance and apparent viscosity, and finally destroying the shear-thinning polymer network structure, resulting in a rapid decrease in viscosity. Under such driving state, the migration of electrophoretic particles is accelerated, and the particle movement speed is increased. Therefore, this application embodiment realizes the dynamic control of the electrophoretic solution performance from the perspective of fluid mechanics and rheology, avoiding the limitations of simply relying on voltage or fixed viscosity liquids.
[0039] It should be noted that the "low shear / high shear" mentioned in this application corresponds one-to-one with the particle motion state: (1) Image holding stage: Particle movement is significantly reduced, corresponding to a lower shear state; (2) Electronic paper refresh stage: Charged particles migrate rapidly in a directional manner under the action of the electric field, and relative motion occurs between the particles and the surrounding fluid, forming a large velocity gradient in the local area, thus generating a local high shear environment. Particle movement is one of the sources of local shear change, and viscosity change, in turn, affects the particle movement speed, and the two are mutually coupled.
[0040] Specifically, the electrophoretic solution of this application includes black electrophoretic particles, white electrophoretic particles, shear-thinning polymer, dispersion stabilizer, charge control agent, and solvent in a certain amount. The shear-thinning polymer exhibits shear-thinning non-Newtonian fluid properties, forming a relatively loose three-dimensional physical network structure without an external alternating electric field, exhibiting significant shear-thinning behavior (it should be noted that even in the presence of an external alternating electric field, this application can establish or maintain its non-Newtonian rheological properties without relying on that alternating electric field). The electrophoretic solution of this application, based on the content of each component, exhibits shear-thinning non-Newtonian fluid properties, not only possessing fast response and low image retention, but also excellent steady-state retention performance and low power consumption. Using the electrophoretic solution of this application in electronic paper can significantly improve the display performance of electronic paper, showing great application potential.
[0041] In some embodiments, the mass percentage of black electrophoretic particles in the electrophoretic solution can be 6-8%, for example, any one or any two values of 6%, 6.5%, 7%, 7.5%, 8%, etc.; the mass percentage of white electrophoretic particles can be 6-8%, for example, any one or any two values of 6%, 6.5%, 7%, 7.5%, 8%, etc.; the mass percentage of shear-thinning polymer can be 2-8%, for example, any one or any two values of 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc.; and the mass percentage of dispersant stabilizer can be 0%. The mass percentage of the charge control agent can be 0.2% to 1.2%, for example, any one or any two values between 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.; the mass percentage of the charge control agent can be 0.2% to 1.2%, for example, any one or any two values between 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, etc.; the remaining amount is solvent, for example: 6% black electrophoretic particles, 6% white electrophoretic particles, 2% shear-thinning polymer, 0.8% dispersant stabilizer, 0.2% charge control agent, 85% solvent (total electrophoretic solution is 100%); and so on.
[0042] In some embodiments, at least a portion of the shear-thinning polymer coats the surface of at least a portion of the black electrophoretic particles to form a coating layer. Simultaneously, at least a portion of the shear-thinning polymer coats the surface of at least a portion of the white electrophoretic particles to form a coating layer. The shear-thinning polymer forms a stable polymer coating layer on the surface of the electrophoretic particles through physical adsorption, association, or chain entanglement, and constructs a loose three-dimensional network structure through bridging interactions between the electrophoretic particles. This allows the electrophoretic particles to participate in the construction of a rheological network, thereby generating significant non-Newtonian shear-thinning behavior under conditions without an applied alternating electric field.
[0043] like Figure 1As shown, the surfaces of black and white electrophoretic particles are coated with a shear-thinning polymer layer, which can form bridges between adjacent electrophoretic particles, constituting a loose, continuous three-dimensional weak physical network structure. At low shear rates (e.g., during the electronic paper image retention stage), based on the coating of the shear-thinning polymer layer and intermolecular interactions, the polymer chains are in an entangled state. This shear-thinning polymer network structure is relatively stable and intact, exhibiting high viscosity, which can reduce electrophoretic particle migration. When the shear rate increases (e.g., during the electronic paper refresh stage), the shear-thinning polymer coating layer network structure can be disrupted under driving conditions. The polymer chains / electrophoretic ion particles align along the flow direction, i.e., the polymer chains undergo orientation and unentanglement, and the network partially disassembles, thereby reducing entanglement and drag, and the viscosity rapidly decreases. Changes in viscosity directly affect the electrophoretic migration speed of the electrophoretic particles, thus enabling dynamic switching between response speed and afterimage control.
[0044] Specifically, rheological properties can be triggered by shearing (without an alternating electric field), and the principle can be explained as follows: (1) Low shear rate (stationary / slow drive): High viscosity → slow migration of electrophoretic particles → maintains stable image. (2) High shear rate (fast refresh): Low viscosity → fast migration of electrophoretic particles → shortens refresh time. Such viscosity change curves conform to the shear-thinning law: η(γ˙)∝γ˙n 1, n < 1; where γ˙ is the shear rate, η is the apparent viscosity, and n is the flow index. The shear rate changes due to the different particle motion states during the refresh and hold phases of the electronic paper. During the refresh phase, rapid particle migration and enhanced local fluid disturbance correspond to higher shear rates; during the hold phase, particles are relatively stable, corresponding to lower shear rates.
[0045] In this embodiment of the application, less than 50 s - ¹The shear rate is defined as a low shear rate, which is greater than or equal to 50 s⁻¹. - The shear rate ¹ is defined as the high shear rate. For example, in some embodiments, the low shear rate can be 1~10 s. - ¹; In specific implementation examples, testing can be performed in 1 second. - ¹Characteristics. The high shear rate in the embodiments of this application can be: 50~100 s - ¹; In specific implementation examples, testing can be performed in 100 seconds. - ¹Characteristics.
[0046] In some embodiments, based on the present application, a shear-thinning polymer that is completely different from existing electrorheological materials is selected. Through the unique network structure of "electrophoretic particle surface coating + particle participation network", the non-Newtonian properties can be stably maintained under the condition of no alternating electric field, and it has a significant effect on reducing image retention and improving response speed.
[0047] In some embodiments, the number-average molecular weight of the shear-thinning polymer is 10,000 to 100,000; for example, the number-average molecular weight of the shear-thinning polymer can be any one or any two values of 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, etc. Within the above-mentioned number-average molecular weight range, there is sufficient chain length, which is beneficial for forming sufficient chain entanglement and weak physical network; at the same time, the system background viscosity is suitable, which is beneficial for the rapid migration of particles during the refresh stage. More preferably, shear-thinning polymers with a number-average molecular weight of 28,000 to 32,000 are more conducive to balancing network formation ability and refresh response performance, and can better meet the characteristics of shear-thinning non-Newtonian fluids, so that the electrophoretic solution has better comprehensive performance of rapid response and low afterimage.
[0048] In some embodiments, the shear-thinning polymer is an amorphous organic polymer. Amorphous organic polymers have better chain segment mobility, making them more prone to reversible association, disentanglement, and orientation, thus facilitating reversible shear-thinning behavior. Compared to highly crystalline polymers with restricted chain segment mobility, amorphous organic polymers exhibit better reversibility in network reconstruction and deconstruction.
[0049] In some embodiments, the molecular structure of the shear-thinning polymer contains functional groups, which form reversible physical crosslinks through hydrogen bonding, π–π stacking, or at least one interaction of zwitterions.
[0050] For example, the functional group urea can form reversible physical crosslinks through hydrogen bonding interactions. The functional group pyrene methyl can form reversible physical crosslinks through π–π stacking interactions. The functional group sulfobetaine can form reversible physical crosslinks through zwitterionic interactions; and so on.
[0051] "Reversible physical crosslinking" mainly refers to physical crosslinking formed by weak interactions, rather than permanent covalent crosslinking. It can spontaneously form in a solvent system at room temperature (25-30°C) relying on weak interactions between polymer molecules. When shear stress increases, these weak interactions can partially dissociate, and the network undergoes reversible deconstruction. When shear stress decreases, the weak interactions can be re-established, and the network recovers. The embodiments of this application utilize the aforementioned functional groups capable of forming reversible weak interactions, thereby enabling shear-thinned polymers to better construct loose three-dimensional network structures in electrophoresis solutions.
[0052] It should be noted that in the electrophoresis solution of this application embodiment, one or more weak interactions may coexist in the same system. For example, some shear-thinning polymers may exhibit hydrogen bonding, as well as hydrophobic association or π-π stacking.
[0053] In some embodiments, the functional groups include at least one selected from ureidinidone end groups, N,N'-bis(C6-14 alkyl)ureido, ureo, pyrene methyl, and sulfobetaine. That is, the molecular structure of the shear-thinning polymer contains at least one functional group selected from ureidinidone end groups, N,N'-bis(C6-14 alkyl)ureido, ureo, pyrene methyl, and sulfobetaine. These functional groups can form reversible weak physical crosslinks, for example, through hydrogen bonding, π–π stacking, or at least one interaction of zwitterions. In other words, the aforementioned functional groups correspond to different types of weak interaction sources.
[0054] The sulfobetaine group is the functional group formed by sulfobetaine (SB). Sulfobetaine, also known as ammonium alkyl sulfonyl lactone, is a trialkylammonium inner salt compound similar to alkyl betaines, except that the alkyl carboxylic acid in carboxylic betaine is replaced by an alkyl sulfonic acid, hence the name (alkyl)sulfobetaine. Specifically, sulfonyl betaines include methacryloylethyl sulfobetaine, dodecyl dimethyl sulfopropyl betaine, tetradecyl sulfopropyl betaine, hexadecyl sulfopropyl betaine, and many others.
[0055] In some embodiments, the shear-thinning polymer includes polyacrylate polymers. Specifically, the shear-thinning polymer includes at least one of ureidopyrimidinone-terminated poly(lauryl methacrylate), N,N'-bis(dodecyl)urea-grafted poly(stearyl methacrylate), 1-pyrene methyl methacrylate-lauryl methacrylate copolymer, and sulfobetaine-functionalized poly(dodecyl methacrylate). Alternatively, it can be a single poly(stearyl methacrylate), which, due to the absence of associating groups (i.e., lacking hydrogen bonds, UPy, urea groups, ionic functional groups, etc.), exhibits less shear-thinning properties than the aforementioned shear-thinning polymers with functional groups.
[0056] Ureidinone-terminated poly(lauryl methacrylate), also known as UPy-terminated poly(lauryl methacrylate) (UPy-PLMA), is a supramolecular functionalized linear homopolymer. It has poly(lauryl methacrylate) (PLMA) as the main chain, with UPy (2-ureido-4[1H]-pyrimidinone) groups covalently linked to the chain ends. It achieves reversible self-assembly through quadruple hydrogen bonds and has the characteristics of strong hydrophobicity, low glass transition temperature, thermally reversible self-healing, and adjustable adhesion and rheology.
[0057] N,N'-bis(dodecyl)urea-grafted poly(stearyl methacrylate), or simply bis(dodecyl)urea-grafted PSMA, is a supramolecular functionalized long-chain alkyl polyacrylate. It has poly(stearyl methacrylate) (PSMA) as the main chain and N,N'-bis(dodecyl)urea (DDU) groups covalently grafted onto it. It self-assembles by relying on strong hydrogen bonds between the urea groups and has properties such as extreme hydrophobicity, low-temperature flexibility, thermally reversible physical crosslinking, rheological tunability, and self-healing.
[0058] 1-Pyrene methyl methacrylate-lauryl methacrylate copolymer (PyMA-co-LMA) is a random / gradient acrylate copolymer that combines strong fluorescence, extreme hydrophobicity, low-temperature flexibility, and polymerizability. It is copolymerized from 1-pyrene methyl methacrylate (PyMA) and lauryl methacrylate (LMA) and belongs to the fluorescently labeled functional polyacrylate category. It can be endowed with strong fluorescence, environmental responsiveness, and π-π stacking effects through the pyrene ring.
[0059] Sulfobetaine-functionalized poly(dodecyl methacrylate) is a block / graft polymer prepared by post-functionalization or copolymerization of a long-chain hydrophobic poly(dodecyl methacrylate) backbone and zwitterionic sulfobetaine side groups. It has multiple properties such as strong hydrophobicity and high hydrophilicity, and is a high-end functional polymer material.
[0060] In some embodiments, the solvent includes an ionic liquid or an organic solvent; wherein the ionic liquid includes at least one of imidazolium ionic liquids, pyridinium ionic liquids, quaternary ammonium salt ionic liquids, quaternary phosphonium salt ionic liquids, and pyrrolidine ionic liquids, and the organic solvent includes an alkane solvent.
[0061] For example, imidazolium ionic liquids can be 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium hexafluorophosphate, etc. Pyridinium ionic liquids can be 1-butylpyridine tetrafluoroborate ([BPy][BF4]), 1-hexylpyridine hexafluorophosphate, etc. Quaternary ammonium ionic liquids can be methyltrioctylammonium chloride (Aliquat 336), tetrabutylammonium nitrate, etc. Quaternary phosphonium ionic liquids can also be tetrabutylphosphonium bis(trifluoromethanesulfonyl)imide, etc. Pyrrolidine ionic liquids can be N-methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide, etc.
[0062] For example, the solvent is a nonpolar organic solvent, such as an alkane solvent. Specifically, the alkane solvent can be an alkane solvent with 10-16 carbon atoms. The organic solvent is a nonpolar alkane solvent, specifically one or more of straight-chain, branched-chain, or isomeric alkanes with 10-16 carbon atoms. For example, it can be an isomeric alkane solvent, such as the Isopar G alkane solvent produced by ExxonMobil.
[0063] In some embodiments, black electrophoretic particles may include at least one of carbon black, copper chromium black, and iron-manganese black; white electrophoretic particles may include at least one of titanium dioxide, silicon dioxide, and aluminum oxide. The aforementioned electrophoretic particles are commonly used particles that readily become charged or readily acquire an electric charge.
[0064] In some embodiments, the dispersion stabilizer may include a fluorocarbon surfactant; conventional dispersion stabilizer materials in the art may be used. For example, fluorinated surfactants include FS-3100, FS-3000, FS-50, FS-63, FS-65, FS-81, etc.
[0065] In some embodiments, the charge control agent (CCA) includes at least one of cationic surfactants, anionic surfactants, nonionic surfactants, and amphoteric surfactants. Conventional charge control agent materials in the art can be used. Specifically, the cationic surfactant can be octadecyltrimethylammonium chloride or N,N-dimethyldodecylamine, etc.; the anionic surfactant can be sodium dodecylbenzenesulfonate, sodium ethoxyethyl sulfate, sodium diisooctyl succinate sulfonate (AOT), etc.; the nonionic surfactant can be alkyl alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether, etc.; and the amphoteric surfactant can be ethoxylated nonylphenol sulfosuccinate disodium salt or dodecyl dimethyl betaine, etc.
[0066] Secondly, embodiments of this application provide a method for preparing an electrophoresis solution. Specifically, as shown in the example... Figure 2 As shown, the preparation method of this application embodiment includes the following steps: S01: Provide the components of the electrophoresis solution in the embodiments of this application.
[0067] S02: The shear-thinning polymer is mixed with black and white electrophoretic particles to obtain coated particles.
[0068] S03: The coated particles and charge control agent are mixed for charge regulation, then added to a solvent, and a dispersant stabilizer is added to obtain an electrophoretic solution.
[0069] In this embodiment, a shear-thinning polymer is first coated and modified with black and white electrophoretic particles to obtain coated particles. These coated particles are then mixed with a charge control agent, solvent, and dispersant stabilizer to form an electrophoretic solution. This preparation method is not only simple and easy to scale up, but the resulting electrophoretic solution also exhibits shear-thinning non-Newtonian fluid characteristics. It features rapid response, low image retention, excellent steady-state retention, and low power consumption. Based on the composition of each component, this shear-thinning non-Newtonian fluid-like electrophoretic solution shows great promise for application in the field of electronic paper.
[0070] Specifically, in step S01, the composition and content ratio of each component are as described above.
[0071] Specifically, in step S02, there are several ways to mix the shear-thinning polymer with the black and white electrophoretic particles. For example, the shear-thinning polymer can be directly mixed and stirred with the black and white electrophoretic particles; or, the shear-thinning polymer can be divided into two parts and mixed separately with the black and white electrophoretic particles, and then mixed together. Alternatively, the shear-thinning polymer can be first dissolved in a portion of a solvent to prepare a polymer stock solution, and then the polymer stock solution can be directly mixed and stirred with the black and white electrophoretic particles; or, the shear-thinning polymer can be first dissolved in a portion of a solvent to prepare a polymer stock solution, and then the polymer stock solution can be divided into two parts and mixed separately with the black and white electrophoretic particles, and then mixed together.
[0072] In some embodiments, this embodiment first prepares a shear-thinning polymer mother liquor by dissolving the shear-thinning polymer in a portion of a solvent, and then adds black and white electrophoretic particles to the shear-thinning polymer mother liquor for coating. Specifically, the shear-thinning polymer is dissolved in a portion of a solvent to obtain a polymer mother liquor with a mass percentage of 4% to 6%. The polymer mother liquor is then divided into two portions (which may be equal in weight) and mixed separately with the black and white electrophoretic particles, and then mixed again. Mixing can be carried out under stirring or low-shear conditions, allowing the shear-thinning polymer to form a stable polymer coating layer on the particle surface through physical adsorption, weak interactions, or chain entanglement, thereby obtaining surface-modified coated particles: coated black particles and coated white particles. The coating layer can form a bridging structure between the electrophoretic particles, allowing the electrophoretic particles to participate in the formation of a loose three-dimensional weak physical network in the system.
[0073] Specifically, in step S03: First, charge control is performed by adding charge control agents (CCA) to the obtained coated black particles and coated white particles respectively. The charge density on the surface of the coated particles is controlled through ion adsorption or counterion pairing, so that the coated black particles and coated white particles acquire stable and opposite charge polarities. Then, the system is assembled and dispersed: the coated black particles and coated white particles treated with charge control agents are added to all the solvents in the formula, and a dispersing stabilizer is added at the same time. The particles are uniformly dispersed under ultrasonic or high-shear dispersion conditions to form a stable electrophoresis solution system.
[0074] Furthermore, the rheological properties of the electrophoretic solution can be tested: for example, by controlling the shear rate of the system, measuring the rheological curves of the electrophoretic solution under low and high shear conditions, and adjusting the amount of each component of the electrophoretic solution according to the requirements of the display refresh stage and the image holding stage, so that the electrophoretic solution system exhibits low viscosity under high shear conditions and high viscosity under low shear conditions.
[0075] For example, by adjusting the amount of shear-thinning polymer added, the electrophoretic solution can exhibit different viscosity characteristics at different shear rates: At low shear rates (image holding stage), a weak physical network structure is formed between shear-thinning polymer chains, resulting in higher system viscosity and thus reducing the disordered migration of electrophoretic particles. At high shear rates (rapid refresh phase), the shear-thinning polymer network structure undergoes reversible deconstruction, reducing system viscosity and decreasing particle migration resistance, thereby increasing the refresh rate.
[0076] The electrophoretic solution prepared in this embodiment exhibits rheological behavior triggered by shear rate, rather than induced by alternating electric field. For example, this embodiment allows for shear rate ranging from 1 to 100 s under conditions without alternating electric field. - ¹Scanning confirmed the shear-thinning curve, and the results showed that the rheological behavior of the electrophoretic solution was triggered by the shear rate.
[0077] In some embodiments, after preparing the electrophoretic solution, the specific method of use includes: injecting the electrophoretic solution into the electronic paper module display structure for encapsulation. Specifically, the prepared electrophoretic solution is encapsulated into microcapsule-type or open-cavity electronic paper modules for use in electronic paper modules. Non-Newtonian electrophoretic solution properties are achieved under conditions without an alternating electric field through "coating with a shear-thinning polymer network on the surface of electrophoretic particles + post-charge control + shear-triggered rheological modulation".
[0078] The electrophoretic solution prepared in this application has the following characteristics in electronic paper modules: dynamic viscosity adjustment: the fluid viscosity is adaptively changed by shear rate, eliminating the need for a complex external alternating electric field control system; improved response speed: viscosity is significantly reduced during the refresh stage, increasing particle migration speed; reduced image retention: viscosity is increased during the hold stage, reducing disordered particle migration; low power consumption: reduced dependence on high driving voltage; strong versatility: suitable for both black-and-white and color electronic paper, and compatible with existing packaging processes. It can function stably under DC drive or conventional electrophoretic display drive conditions.
[0079] Thirdly, embodiments of this application provide an electronic paper module. Specifically, the electronic paper in this application embodiment contains the electrophoretic solution provided in the first aspect of this application embodiment or the electrophoretic solution prepared by the preparation method provided in the second aspect of this application embodiment.
[0080] The electronic paper module of this application embodiment is equipped with the electrophoretic liquid unique to this application embodiment. The electrophoretic liquid can exhibit significant shear thinning behavior under conditions without an external alternating electric field, thereby enabling the electronic paper module to display advantages such as fast response speed, low image retention, and good steady-state retention performance.
[0081] Specifically, an electrophoretic solution with a shear-thinning (pseudoplastic) non-Newtonian fluid formulation is introduced into the electronic paper module. By changing the viscosity of the system under different shear drive speeds, the migration speed of electrophoretic particles is dynamically adjusted, thereby improving the response speed, afterimage, and white field brightness of the electronic paper display module.
[0082] In some embodiments, the electronic paper module may employ a microcapsule-type or microcup-type electrophoretic display structure.
[0083] For example, the electrophoretic solution can be encapsulated in microcapsules, coated onto a film, and assembled into an electronic paper module. Alternatively, the prepared electrophoretic solution can be encapsulated in a display cavity formed by a transparent upper electrode substrate and a lower electrode driving substrate.
[0084] The upper substrate may include an ITO transparent conductive layer, and the lower substrate may include a TFT driving array, an electrode layer, and a pixel isolation structure. The electrophoretic solution is encapsulated in the display cavity through liquid injection, lamination, and edge sealing processes to form an electronic paper display module. Under the action of the driving electric field, charged electrophoretic particles undergo directional migration, thereby realizing image display.
[0085] Fourthly, embodiments of this application provide a display device. Specifically, the display device of this application includes the electronic paper module provided in the third aspect of this application. The display device based on this application uses the electronic paper module unique to this application, thereby having excellent display performance.
[0086] In some embodiments, the display device includes electronic paper to which an electronic paper display module is fixed.
[0087] In summary, the embodiments of this application introduce a shear-thinning polymer with reversible weak physical crosslinking into the electrophoretic solution and enable electrophoretic particles to participate in the construction of a shear-response network structure, thereby achieving significant shear-thinning behavior under conditions without an external alternating electric field. This simultaneously improves image retention, response speed, and steady-state retention performance. Electrophoretic solutions utilizing these rheological properties can be used in applications that improve electronic paper refresh speed, reduce image retention, and lower power consumption.
[0088] The following description is based on specific embodiments.
[0089] Example 1 An electrophoretic solvent comprises the following components in weight percentage: 7% black electrophoretic particles (selected carbon black), 7% white electrophoretic particles (selected titanium dioxide), 2% shear-thinning polymer (selected UPy terminal poly(lauryl methacrylate)), 0.8% dispersant stabilizer (selected fluorocarbon surfactant Fluorad™ FC-171), 1.2% charge control agent (selected AOT), and the balance being 82% solvent (selected Isopar G).
[0090] The preparation steps of the above electrophoretic solution include: dissolving the shear-thinning polymer in a portion of the solvent Isopar G (preparing a polymer stock solution with a concentration of 5 wt%), then adding black and white electrophoretic particles, and stirring at 200 rpm for 30 min to allow the shear-thinning polymer to form a coating layer on the surface of the electrophoretic particles. Then, adding the charge control agent AOT and continuing stirring for 20 min allows the particles to acquire a stable charge. Finally, adding the remaining solvent and dispersing stabilizer, dispersing at 6000 rpm for 5 min, and sonicating for 10 min yields a homogeneous electrophoretic solution.
[0091] Example 2-10 An electrophoretic solution and its preparation method differ from Example 1 in that the content or type of shear-thinning polymer is different, as detailed in Table 1. Otherwise, they are the same as in Example 1.
[0092] Comparative Example 1 An electrophoretic solution, differing from Example 1 in that the shear-thinning polymer is replaced with hydrogenated castor oil (an electrorheological material), while the other components and their contents are the same as in Example 1.
[0093] Comparative Example 2 An electrophoretic solution, differing from Example 1 in that the shear-thinning polymer is replaced with polyamide wax (an electrorheological material), while the other components and their contents are the same as in Example 1.
[0094] Comparative Example 3 An electrophoretic solution, differing from Example 1 in that the shear-thinning polymer is replaced with polyisobutylene (an electrorheological material), while the other components and their contents are the same as in Example 1.
[0095] Table 1
[0096] Performance testing The above-described embodiments and comparative examples were evaluated under the same testing platform and environmental conditions. Unless otherwise specified, the black / white electrophoretic particle system, solvent system, charge control agent, and dispersion stabilizer were consistent for all samples.
[0097] Further experiments in this application revealed that, within the molecular weight range defined in the embodiments of this application, the number-average molecular weight of the shear-thinning polymer has a significant impact on the image retention effect of the electrophoretic solution. When the molecular weight increases from 10,000 to around 32,000 (e.g., 28,000~32,000), the formed physical network structure is more complete, the detangling under high shear is more thorough, the viscosity decreases more significantly, and the image retention shows a decreasing trend. Even when the molecular weight continues to increase to around 100,000, good stage stability is still maintained. However, shear-thinning polymers with a molecular weight in the range of 28,000~32,000 exhibit the best overall performance in terms of rapid response and low image retention.
[0098] (1) Rheological testing Test objective: The study evaluates the shear-dependent rheological behavior of the electrophoretic solution under conditions without alternating electric field, verifies the existence of "shear-triggered shear thinning (pseudoplastic) non-Newtonian properties", and provides data support for the dynamic viscosity switching during the "refreshing phase / holding phase".
[0099] Test conditions: The rheological test used steady-state shear scan, with a shear rate of 1→100 s. - ¹, temperature 25±2℃, average value was taken after each shear point stabilized for 10 s, no alternating electric field.
[0100] Evaluation indicators: η(1 s - ¹): Low shear apparent viscosity (corresponding to the holding phase); η(100 s - ¹): High shear apparent viscosity (corresponding to the rapid refresh stage); viscosity decrease rate: η(1s) - ¹) η(100s - ¹) / η(1s - ¹); Magnification: η(1s) - ¹) / η(100s- ¹); Key criteria for judgment: The larger the multiplier and the greater the decrease, the stronger the dynamic control capability, which is more in line with the purpose of "shear-triggered rheological control" in this application.
[0101] (2) Cyclic afterimage test (10 cycles of black and white afterimages) Test objective: The evaluation assesses whether electrophoretic particles fully return to their original positions after multiple switching under standard driving conditions, thereby reflecting the afterimage level and bistable state retention capability.
[0102] Test conditions: Drive voltage: ±15 V; Drive frequency: 60 Hz; Test temperature: 25℃; Drive mode: full white – full black – full white cycle switching 10 times; Measurement: After the 10th switching, the residual gray value of the display unit is measured and normalized with the theoretical maximum gray value to obtain the percentage of image retention.
[0103] Judgment criteria: Ghosting ≤ 1.5%: Ghosting is difficult to detect with the naked eye, excellent; 1.5% < ghosting ≤ 2.5%: Good / Qualified, meets general application requirements; 2.5% < ghosting ≤ 3.5%: Generally acceptable / critically acceptable; Ghosting > 3.5%: Poor quality, ghosting is obvious and easily perceived by users.
[0104] (3) Fast refresh afterimage test Test objective: Simulating the "fast page turning / continuous refresh" scenario of e-paper, this study evaluates whether ghosting accumulates with repeated refreshes under high-frequency refresh rates, and verifies whether the rheodynamic network can deconstruct and recover in a timely manner under high shear / high refresh rates (demonstrating the advantages of shear triggering).
[0105] Test conditions: Refresh method: fast switching between all white and all black (or fast refresh mode of the target waveform); refresh frequency: 3-5 Hz; refresh count: 200 times; test temperature: 25℃; electric field conditions: DC drive or fast refresh waveform (without introducing alternating electric field to induce "current conversion").
[0106] Evaluation indicators and standards: Metric: ΔL* (brightness difference / grayscale difference before and after fast refresh), and record whether it accumulates with the number of refreshes.
[0107] Judgment criteria: ΔL*≤1.5: Excellent (virtually invisible); 1.5 < ΔL* ≤ 2.5: Pass; ΔL*>2.5: Unacceptable (obvious background haze); At the same time, if the risk "accumulates significantly with repeated occurrences", even if ΔL* is critical, it is still considered risky / unstable.
[0108] Finally, the rheological test results are shown in Table 2, and the cyclic image retention test results (including response time) and fast refresh image retention test results are shown in Table 3. Response time refers to the time required for the electronic paper display unit to switch from its initial display state to the target display state and reach 90% of the target steady-state brightness (or grayscale value) under standard driving conditions. This time is obtained during the response test steps of the display unit switching between full white and full black or full black and full white, and is used to characterize the dynamic refresh performance of the electrophoretic solution system.
[0109] Table 2
[0110] Figure 3 This is a comparison graph of the viscosity of the electrophoretic solution as a function of shear rate in Example 3 and Comparative Example 1 of this application. The horizontal axis represents the shear rate (s). 1 ), range 1~100 s 1 The vertical axis represents apparent viscosity (Pa). (s). Comparison of the rheological curves of the electrophoresis solution shows that the viscosity of the electrophoresis solution in Example 3 can reach as high as 5.30 Pa at low shear rates. The viscosity decreases sharply with increasing shear rate, especially at high shear rates of 100 s. 1 The viscosity decreased to 0.78 Pa. The viscosity of the electrophoretic solution in Comparative Example 1 exhibits typical shear-thinning characteristics, while the viscosity of the electrophoretic solution only decreases from 1.12 Pa across the entire shear rate range. s decreased slightly to 0.94 Pa The curve is flat, exhibiting near-Newtonian fluid characteristics with no obvious shear-thinning behavior. This comparative result directly verifies that the electrophoretic solution in the embodiments of this application possesses the rheological advantages of low viscosity and rapid response during the refresh phase, and high viscosity and suppression of residual images during the maintenance phase.
[0111] Table 3
[0112] The data in Tables 2 and 3 show that: in Comparative Example 1, the shear thinning is weak without an alternating electric field, the residual image is obvious and easily accumulates, and the steady-state consistency is poor. This indicates that the non-Newtonian structure of this type of system is more dependent on electric field induction and is prone to local particle retention and residual image accumulation (characteristics of electrorheological paths); in Comparative Example 2, the residual image is still large and the fast brush accumulation is obvious, indicating that simply changing the type of electrorheological material cannot fundamentally solve the problem of "residual image accumulation / steady-state fluctuation" and is still affected by the electrorheological network structure and particle retention; in Comparative Example 3, polyisobutylene mainly shows overall viscosity increase and shear thinning is not significant, resulting in a slower response; although the residual image is lower than that of the first two comparative examples, it is still critical and has an accumulation trend, making it difficult to achieve both "fast response + low residual image".
[0113] In the embodiments of this application, significant shear-triggered rheological behavior is exhibited under conditions without an alternating electric field, combining the advantages of fast response, low residual image, and steady-state consistency. Specifically, the electrophoretic solutions prepared in Examples 1-10 of this application all exhibit significant shear-thinning characteristics under conditions without an external alternating electric field, and their overall performance is superior to that of the comparative example. Among them, as the shear ratio of the system increases, the response time shortens, and the cyclic residual image and fast brush residual image decrease, indicating that this type of system can better balance refresh response, residual image control, and steady-state retention performance. Examples 3-5 have better overall performance, especially Example 3, which performs best with a response time of 198 ms, a cyclic residual image of 1.1%, and a fast brush residual image ΔL* of 0.9, with no significant accumulation. Examples 1-2, 7-8, and 10 also show good overall performance. Although the overall performance of Examples 6 and 9 is slightly lower, they are still better than the comparative example overall. Furthermore, as shown in Example 6, when the content of the shear-thinning polymer is too high, the system still has good image retention suppression ability. However, due to the increased background viscosity of the system, the particle migration resistance during the refresh stage increases, thus lengthening the response time. Overall, however, it is still superior to the comparative example. Additionally, Figure 4 These are images showing the afterimages of the electrophoretic solutions in Examples 1-10 and Comparative Examples 1-3 of this application. The actual visual effect of the fast brushing is basically consistent with the fast brushing ΔL* data in Table 3.
[0114] The above results indicate that the electrophoretic solution with a shear-thinning polymer system used in the embodiments of this application can effectively improve the rheological behavior and display performance of the electrophoretic solution.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. An electrophoretic solution, characterized in that, Based on the total mass of the electrophoresis solution as 100%, the electrophoresis solution comprises the following components by mass percentage: Black electrophoretic particles 6-8%; White electrophoretic particles 6-8%; Shear-thinning polymers: 2-8%; Dispersant stabilizer 0.8~1.5%; Charge control agent 0.2~1.2%; The remaining amount is solvent; The shear-thinning polymer exhibits shear-thinning non-Newtonian fluid properties.
2. The electrophoresis solution as described in claim 1, characterized in that, At least a portion of the shear-thinning polymer is coated on the surface of at least a portion of the black electrophoretic particles to form a coating layer, and / or at least a portion of the shear-thinning polymer is coated on the surface of at least a portion of the white electrophoretic particles to form a coating layer.
3. The electrophoresis solution as described in claim 1, characterized in that, The number-average molecular weight of the shear-thinning polymer is 10,000 to 100,000.
4. The electrophoresis solution as described in claim 1, characterized in that, The shear-thinning polymer is an amorphous organic polymer.
5. The electrophoresis solution as described in claim 1, characterized in that, The molecular structure of the shear-thinning polymer contains functional groups, which form reversible physical crosslinks through at least one of hydrogen bonding, π–π stacking, and zwitterionic interactions.
6. The electrophoresis solution as described in claim 5, characterized in that, The functional groups include at least one of ureidopyrimidinone terminal group, N,N'-bis(C6~14 alkyl)ureido, ureo, pyrene methyl, and sulfobetaine.
7. The electrophoresis solution according to any one of claims 1-6, characterized in that, The shear-thinning polymer includes at least one of ureidopyrimidinone-terminated poly(lauryl methacrylate), N,N'-bis(dodecyl)urea-grafted poly(stearyl methacrylate), 1-pyrene methyl methacrylate-lauryl methacrylate copolymer, and sulfobetaine-functionalized poly(dodecyl methacrylate).
8. The electrophoresis solution according to any one of claims 1-6, characterized in that, The solvent includes ionic liquids or organic solvents; wherein the ionic liquid includes at least one of imidazolium ionic liquids, pyridinium ionic liquids, quaternary ammonium salt ionic liquids, quaternary phosphonium salt ionic liquids, and pyrrolidine ionic liquids, and the organic solvent includes alkane solvents.
9. The electrophoresis solution according to any one of claims 1-6, characterized in that, The black electrophoretic particles include at least one of carbon black, copper chromium black, and iron manganese black. And / or, the white electrophoretic particles include at least one of titanium dioxide, silicon dioxide, and aluminum oxide.
10. A method for preparing an electrophoretic solution, characterized in that, include: Provide each component of the electrophoresis solution as described in any one of claims 1-9; The shear-thinning polymer is mixed with the black electrophoretic particles and the white electrophoretic particles to obtain coated particles; The coated particles and the charge control agent are mixed for charge regulation, then added to the solvent, and the dispersing stabilizer is added to obtain the electrophoretic solution.
11. The preparation method according to claim 10, characterized in that, The mixing process includes: dissolving the shear-thinning polymer in a portion of the solvent to obtain a polymer mother liquor with a mass percentage of 4% to 6%, and then dividing the polymer mother liquor into two portions and mixing and stirring them separately with the black electrophoretic particles and the white electrophoretic particles.
12. An electronic paper module, characterized in that, The electronic paper module contains the electrophoretic solution as described in any one of claims 1-9 or the electrophoretic solution prepared by the preparation method described in any one of claims 10-11.
13. A display device, characterized in that, Includes the electronic paper module as described in claim 12.